Analysis of Open Stub Resonator and its Application in Dual Isolation Band of SPDT Switch Design - M. Y. Algumaei; N. A. Shairi; Z. Zakaria; A. M. S. Zobilah; B. H. Ahmad (Institute of Advanced Engineering and Science, 2016)
In this paper, an analysis of open stub resonator is presented and its application in dual isolation band of Single Pole Double Throw (SPDT) switch is proposed. A mathematical model and the characteristic of the bandstop of the resonator were analyzed and discussed. The open stub resonator was implemented using the microstrip transmission line and able to switch between bandstop and allpass responses. Frequency bands of 2.3 and 3.5 GHz were chosen to demonstrate the dual isolation band in the switch design. The performance results of the SPDT switch showed that the isolation was greater than 30 dB, return loss was greater than 10 dB and insertion loss less than 2 dB at the center resonant frequency of 2.3 and 3.5 GHz. The potential application of the proposed dual isolation band of SPDT switch is for multi band RF front-end system such as WiMAX, LTE, WiFi and HyperLAN.